Development of pathway-oriented screening to identify compounds to control 2-methylglyoxal metabolism in tumor cells - Kouichi Yanagi; Toru Komatsu; Yuuta Fujikawa; Hirotatsu Kojima; Takayoshi Okabe; Tetsuo Nagano; Tasuku Ueno; Kenjiro Hanaoka; Yasuteru Urano (Communications Chemistry, 2023)
Abstract Controlling tumor-specific alterations in metabolic pathways is a useful strategy for treating tumors. The glyoxalase pathway, which metabolizes the toxic electrophile 2-methylglyoxal (MG), is thought to contribute to tumor pathology. We developed a live cell-based high-throughput screening system that monitors the metabolism of MG to generate d-lactate by glyoxalase I and II (GLO1 and GLO2). It utilizes an extracellular coupled assay that uses d-lactate to generate NAD(P)H, which is detected by a selective fluorogenic probe designed to respond exclusively to extracellular NAD(P)H. This metabolic pathway-oriented screening is able to identify compounds that control MG metabolism in live cells, and we have discovered compounds that can directly or indirectly inhibit glyoxalase activities in small cell lung carcinoma cells.